Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.9734/cjast/2019/v32i630037
|View full text |Cite
|
Sign up to set email alerts
|

Indigestible Plastic Bags are Hindering Profitability of Dairy Production in Peri-Urban Kampala

Abstract: Many Ugandans living in the urban and peri-urban areas have started dairy farming to tap into the demand for milk and its products, driven by the population growth. Unfortunately, they operate on a small scale because land and cattle feeds in the urban and peri-urban areas are limited. In addition, the peri-urban areas are contaminated with indigestible materials such as plastic bags which once consumed by the cattle impair health, cause loss of milk productivity and death. This report documents the findings f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…3d). Tayebwa et al (Tayebwa et al 2019) reported that cattle farm located in proximity with plastic wastes recycling facility in a peri-urban part of Uganda suffered from serious cases of plastic ingestion. Under such circumstances, farmers (i.e., animal keepers) may be aware of the risks posed by these poorly managed wastes on livestock population, but are constrained by lack of required support and facilities to tackle it, as shown by the work of Nongcula et al ((Nongcula et al 2020) in a South African province of Eastern Cape.…”
Section: Discussionmentioning
confidence: 99%
“…3d). Tayebwa et al (Tayebwa et al 2019) reported that cattle farm located in proximity with plastic wastes recycling facility in a peri-urban part of Uganda suffered from serious cases of plastic ingestion. Under such circumstances, farmers (i.e., animal keepers) may be aware of the risks posed by these poorly managed wastes on livestock population, but are constrained by lack of required support and facilities to tackle it, as shown by the work of Nongcula et al ((Nongcula et al 2020) in a South African province of Eastern Cape.…”
Section: Discussionmentioning
confidence: 99%